Correlation of Chronic Fatigue with Post-Traumatic Stress Disorder and Symptom Severity in COVID-19 Survivors: A Cross-Sectional Study: Correlation of Chronic Fatigue with PTSD - Sarwar, Hassan; Zaheer, Anna; Fatima, Sahar; Parveen, Sumaira (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Corona virus (COVID-19) is an airborne contagious respiratory disease. Fatigue is much reported complain by post-COVID patients. COVID-19 had generated stress in a wide variety of patients can be termed as post-traumatic stress disorder. Objective: To find the correlation of chronic fatigue with post-traumatic stress disorder and symptom severity in COVID-19 survivors. Methods: The commencement of this study required the allowance from University of Lahore ethical committee. About 155 participants participated in this cross-sectional study who had been COVID-19 positive for once up till now, which had supportive evidence through reverse transcriptase polymerase chain reaction (RT-PCR) test. Only those participants got eligible for study who had survived COVID-19 infectious disease. The data were kept secured by negating any biasness. Results: From total of 155 COVID-19 survivors, 75 (48.39%) males and 80 (51.31%) females participated in study. Mean age was 29.32 ± 10.81. About 123 (79.35%) had symptomatic COVID-19. Majority of patients 79 (50.97%) self-categorized them as struggling with moderate symptoms during their quarantine period. About 114 (73.54%) self-perceived they accompanied fatigue after recovering from COVID-19.While 87 (56.13%) COVID-19 survivors had encountered high impact post-traumatic stress disorder. Conclusions: It was concluded that majority of COVID-19 survivors had moderate level of fatigue and high impact post-traumatic stress disorder. This was seen more commonly among females. This is an important finding which needs to be taken into consideration when making a treatment plan for patients